Non-Alcoholic Fatty Liver Disease in Primary Hypothyroidism - Ahmed, Nasir Uddin; Kabir, Md Anwarul; Kalam, Farzana; Akter, Shaheda (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: Non-alcoholic fatty liver disease (NAFLD) is the most common chronic liver condition world-wide. Hypothyroidism is also a common disorder affecting general population especially in women. Objectives: To determine the association between primary hypothyroidism and NAFLD. Materials and Method: This is a cross-sectional descriptive type of observational study where 100 cases of primary hypothyroidism in age group 15-75 years of both sexes were selected from February 2018 to January 2019 in CMH Momenshahi having higher level of Thyroid stimulating hormone(TSH). In all cases ultra-sonogram of hepatobiliary system was done by efficient sonologist who was blind about clinical scenario of the patients. Results: Mean age of patients 29±SD7.57.Among 100 cases 56(56%) having NAFLD among them 95% were female and 5% were male. Conclusion: NAFLD was significantly correlated with primary hypothyroidism. JAFMC Bangladesh. Vol 15, No 2 (December) 2019: 206-208